Automated Traffic Signal Performance Measure Workshop 2016
DOI: 10.5703/1288284316047
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Performance Measures for Practitioners to Triage Split Failure Trouble Calls

Abstract: Overview of Study LocationThe location used to demonstrate the use of the Abstract Graphical Performance Measures for Practitioners to Triage Split Failure Trouble CallsDetector occupancy is commonly used to measure traffic signal performance. Despite improvements in controller computational power, there have been relatively few innovations in occupancy-based performance measures or integration with other data. This paper introduces and demonstrates the use of graphical performance measures based on detector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…One limitation of GOR is that it tends to become saturated at relatively moderate levels of demand ( 10 ). Freije et al found that combining GOR with the occupancy rate of the first N seconds of red, which was called the red occupancy ratio (ROR), could be used to identify the occurrence of split failures ( 11 ). The researchers found that when both GOR and ROR were high, it was likely that a split failure occurred; a value of N = 5 s and 80% thresholds for GOR and ROR were found to work well in the initial study for identifying potential split failures.…”
Section: Split Failure Estimation Using Occupancy Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of GOR is that it tends to become saturated at relatively moderate levels of demand ( 10 ). Freije et al found that combining GOR with the occupancy rate of the first N seconds of red, which was called the red occupancy ratio (ROR), could be used to identify the occurrence of split failures ( 11 ). The researchers found that when both GOR and ROR were high, it was likely that a split failure occurred; a value of N = 5 s and 80% thresholds for GOR and ROR were found to work well in the initial study for identifying potential split failures.…”
Section: Split Failure Estimation Using Occupancy Ratiosmentioning
confidence: 99%
“…In this paper, this is referred to as the first N seconds of red. Freije et al ( 11 ) suggested the use of N = 5.…”
Section: Split Failure Estimation Using Occupancy Ratiosmentioning
confidence: 99%
“…ATSPMs provide extensive insights into signal functionality because they rely on continuous high-resolution signal controller data. Several studies have attested to the mobility benefits brought forth by these systems ( 1 7 ). Day et al.…”
Section: Introductionmentioning
confidence: 99%
“…Attendees were asked to respond to the questions with the following scale: 5 Strongly Agree 4 Agree 3 Neutral 2 Disagree 1 Strongly Disagree Figure 4.3 shows the distribution of public sector and consultant attendees at the workshop. Thirty-nine participants returned the survey, and the majority self-identified as consultants.…”
Section: Chapter 4: Forumsmentioning
confidence: 99%